The traffic modelling in cities taking into account the network of motor transport parking - Лобашов, Олексій Олегович; Прасоленко, Олексій Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Problem of the traffic modelling in cities on the example of Kharkiv is considered . In contrast to the known methods of modeling proposed to take into account the network of motor transport parking.